Nonlinear Modes in Shear Horizontal Wave Propagation–Analytical and Numerical Analysis. (8th December 2022) - Osika, M.; Ziaja-Sujdak, A.; Radecki, R.; Cheng, L.; Staszewski, W.J.
Abstract: Nonlinear shear horizontal guided wavefield is investigated analytically in plates. The major focus is on the effect of nonlinear material parameters, excitation frequency, wave number and wave amplitude on nonlinear mode generation. The analytical solution is based on the multiple-scale perturbation method and modal decomposition approach. The approximate analytical solution is validated using the Local Interaction Simulation Approach, implemented for nonlinear shear wave propagation. The results show that the analysed shear horizontal wavefield is distorted by material nonlinearity. The resulting displacement field can be interpreted in a form of nonlinear modes. Highlights: Nonlinear shear horizontal guided wavefield is investigated analytically in plates. Nonlinear material parameters, excitation frequency, wave number and amplitude are analysed. The solution is based on the multiple-scale perturbation method and modal decomposition. The approximate solution is validated using the Local Interaction Simulation Approach. The results show that the analysed wavefield is distorted by material nonlinearity and can be interpreted in a form of nonlinear modes.